1968
DOI: 10.1039/c19680001496
|View full text |Cite
|
Sign up to set email alerts
|

trans-Effect order for alkene, alkyne, phosphine, arsine, stibine, and sulphide ligands from studies of diethylamine exchange reactions of L,PtCl2,[14C]NHEt2 in various solvents

Abstract: THE position of alkynes in the trans-effect series for platinum(r1) complexes has not been reported, nor have the relative positions of substituted phosphines, arsines, and stibines been established.We report the results of kinetic studies of diethylamine exchange reactions at 25" in complexes of the type tran~-l,PtCl,[~~C]NHEt~ (I, = ligand) in methanol (Figure l), n-hexane (Figure Z), and benzene. The reaction products have been shown by spectra to be identical with the starting material.The order of decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Odell and co-workers demonstrated that alkene and alkyne showed highest trans effect than any other compounds in platinum complexes (trans effect: C 2 H 4~i PrCH= CHMe~Me 2 C(OH)C C-C(OH)Me 2 @ Et 3 Sb > Ph 3 Sb > Me 3 P > Et 3 P > Ph 3 P). [20] Our proposed decay mechanism is shown in Scheme 2. First, cyclohexene will complex with cationic gold to form a goldalkene p complex, then, because of the trans effect of the www.chemeurj.org alkene, the phosphine ligand will be temporarily replaced to form complex 2 and free AuOTf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Odell and co-workers demonstrated that alkene and alkyne showed highest trans effect than any other compounds in platinum complexes (trans effect: C 2 H 4~i PrCH= CHMe~Me 2 C(OH)C C-C(OH)Me 2 @ Et 3 Sb > Ph 3 Sb > Me 3 P > Et 3 P > Ph 3 P). [20] Our proposed decay mechanism is shown in Scheme 2. First, cyclohexene will complex with cationic gold to form a goldalkene p complex, then, because of the trans effect of the www.chemeurj.org alkene, the phosphine ligand will be temporarily replaced to form complex 2 and free AuOTf.…”
Section: Resultsmentioning
confidence: 99%
“…And alkenes/alkynes are indeed the ligands that have shown the strongest trans effect. Odell and co‐workers demonstrated that alkene and alkyne showed highest trans effect than any other compounds in platinum complexes ( trans effect: C 2 H 4 ∼ i PrCHCHMe∼Me 2 C(OH)C≡C‐C(OH)Me 2 ≫Et 3 Sb>Ph 3 Sb>Me 3 P>Et 3 P>Ph 3 P) 20…”
Section: Resultsmentioning
confidence: 99%
“…equivalents of the P-alkane ligand 6 (~5 mins, 20 °C) affords only trans-[PdCl(Me)(κ 1 -P-6) 2 ] (10) (δ 31 P 6.7 ppm). To account for the formation of 4 and 9 it is proposed that initially [PdCl(Me)(κ 2 -P,C-2)] (10) is formed, which undergoes rapid chloride ligand substitution (labilised by the 5 trans alkene moiety 29 ) by 2 to form complex 11. In the presence of free ligand 2, complex 11 then undergoes pseudoreductive elimination affording phosphonium salt 9 and Pd 0 complex 4 (Scheme 6).…”
mentioning
confidence: 99%
“…An interesting example of the importance of the solvent on the substitution pathways of Pt(II) complexes has been given by Odell [10]. …”
Section: Platinum(ii) Complexesmentioning
confidence: 99%